Pediatric dermatology II inflammatory dermatoses - Cohen, Bernard, 1951-; Swinyer, Leonard J., 1940-; Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1989)
(Producer) This program is a companion set to Pediatric dermatology I featuring presentations of inflammatory dermatoses in children
'From the collections of Bernard Cohen ... and Leonard J. Swinyer.'
Keywords: Dermatitis -- infant; Dermatitis -- child